A ROBUST EIGHT–MEMBERED RING MOTIF IN THE HYDROGEN-BONDED STRUCTURE OF -(PHENYLAMINO)PYRIDINIUM- DI(METHANESULFONYL)AMIDATE - Karna Wijaya; Iqmal Tahir; Armand Blaschette; Oliver Mours; Peter G Jones (Universitas Gadjah Mada, 2002)
The compound was prepared by dissolving 2-(phenylamino)pyridine (0.52 g ; 3.0 mmol) and di(methanesulfonyl)amine (0.51 g; 3.0 mmol) in 5 mL methanol. Slow partial evaporation of the solvent at low tempertaure (-30 oC) gave a yield of 0.66 g (64%) and crystals suitable for X-ray study (m.p. 150-152 oC). The single crystal X-ray result showed that the crystal system was trikline with space group P1. The crystal structure of the title compound 2-(phenylamino)pyridinium-di(methane-sulfonyl)amidate forms a robust antidromic ring motif type R228. The structure testifies to the persistence of the R228 in question, which was previously detected as a robust supramolecular synthon in 2-aminopyridinium di(benzenesulfonyl)amidate and in a series of onium di(methane-sulfonyl)amidates.